On Correlation of Absence Time and Search Effectiveness - Chakraborty, Sunandan; Radlinski, Filip; Shokouhi, Milad; Baecke, Paul (Proceedings of the ACM International Conference on Research and Development in Information Retrieval (SIGIR), 2014)
Online search evaluation metrics are typically derived based on implicit feedback from the users. For instance, computing the number of page clicks, number of queries, or dwell time on a search result. In a recent paper, Dupret and Lalmas introduced a new metric called absence time, which uses the time interval between successive sessions of users to measure their satisfaction with the system. They evaluated this metric on a version of Yahoo! Answers. In this paper, we investigate the effectiveness of absence time in evaluating new features in a web search engine, such as new ranking algorithm or a new user interface. We measured the variation of absence time to the effects of 21 experiments performed on a search engine. Our findings show that the outcomes of absence time agreed with the judgement of human experts performing a thorough analysis of a wide range of online and offline metrics in 14 out of these 21 cases. We also investigated the relationship between absence time and a set of commonly-used covariates (features) such as the number of queries and clicks in the session. Our results suggest that users are likely to return to the search engine sooner when their previous session has more queries and more clicks.